New and Efficient Synthesis of 2,3,4-Trisubstituted 2H-Pyrrolo[3,4-c]quinolines via a MCR/Staudinger/Aza-Wittig Sequence - Qu, Feng; Hu, Ruo-Fei; Gao, Le; Wu, Jing; Cheng, Xiao-Hong; Wang, Song; He, Ping (Synthesis, 2015)
A new and efficient method for the construction of 2,3,4-trisubstituted 2H-pyrrolo[3,4-c]quinoline derivatives was developed. Starting from easily accessible 2-azidobenzaldehyde, nitromethane, 1,3-dicarbonyl compounds, and various amines gave the multicomponent reaction (MCR) products, 1-substituted 3-acyl-4-(2-azidophenyl)-2-methyl-1H-pyrroles, that underwent Staudinger/aza-Wittig cyclization of in the presence of triphenylphosphine to give the final products.
Keywords: 2H-pyrrolo[3,4-c]quinolones; multicomponent reaction; azide; aza-Wittig reaction; iminophosphorane